Karakteristik Fisik, Kimia, Dan Sensori Gel Distribusi Spasial Lemak Sebagai Model Pangan - Ardi Manggala Putra; Prihatin Prihatin; Nur Hardina (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2025)
This study aims to obtain gelatin agar gel emulsion as a food model to control the spatial distribution of fat and determine its sensory profile. This study used a completely randomized design with five treatments, namely heterogeneous gel 1 (GTH1), homogeneous gel 1 (GHM1), heterogeneous gel 2 (GHT 2), homogeneous gel 2 (GHM 2), homogeneous gel 3 (GMH3) and analyzed variance (ANOVA) followed by Duncan test of significance p<0.05. The best spatial distribution treatment of fat in gel emulsion was selected based on fat content, water content, organoleptic tests including hardness, color, elasticity, Gel Strenght, and Adhesiveness. The results showed that the homogeneous gel treatment II had a good value. This is indicated by the measurement results of fat content of 3.84%, moisture content of 78.07%, organoleptic test of hardness 7.4 (like), color 7.1 (like), suppleness 7.2 (like), gel strength 38.7751 (gr/cm2), and adhesiveness -10.754 g/force. Spatial distribution of fat in the best emulsion gel is homogenous gel 2 (GHM2) with fat content of 3.84%, water content of 78.07%, organoleptic tests include hardness 7.4 (liked by panelists), color 7.1 (liked by panelists), suppleness 7.2 (liked by panelists), gel strength 38.7751 (gr/cm2), and adhesiveness -10.754 g/force. Emulsion gel with homogeneous fat distribution GHM2 is the best formulation to produce a low-fat gel with sensory characteristics favored by panelists and optimal texture structure.